UPAYA MENINGKATKAN KEMANDIRIAN DAN MINAT BELAJAR IPAS MENGGUNAKAN MODEL SELF DIRECTED LEARNING BERBANTUAN MEDIA AUGMENTED REALITY KELAS VI SD NEGERI 2 SIBRAMA - Bahri, Valdis Gusri; Nugroho, Agung (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to increase the independence and interest in learning of grade VI elementary school students in IPAS subjects through the application of the Self-Directed Learning model with the help of Augmented Reality media. The research used the method of classroom action research (PTK), which was conducted in two cycles with the research subjects of grade VI students of SDN 02 Sibrama. Data collection was done through questionnaires, interviews, and observations, which were then analysed quantitatively and qualitatively. Based on the results of the study, the average level of student learning independence in Cycle I was still sufficient, namely 72%, while student interest in learning was 74% which did not meet the success criteria. After the improvement of learning in cycle II there was an increase in learning independence to 82% and interest in learning reached 81% with an increase in learning independence by 10% and interest in learning by 7%. The conclusion of this study shows that the use of the Self-Directed Learning model with the help of augmented reality media can effectively increase student independence and interest in learning.